PERAN INSTAGRAM DALAM PARTISIPASI POLITIK GENERASI MUDA DI PEMILU 2024 - , Natasya Aulia; Yulita Nilam Fridiyanti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Abstract The engagement of younger generations in political matters is a frequent topic of discussion in society. Millennials and Generation Z are often perceived as showing limited interest in political life, which is evidenced by their lack of engagement with political issues, low trust in political institutions, and skepticism towards government and its officials. However, millennials in Indonesia have emerged as leaders in the extensive use of social media. Their participation in today’s digital era offers millennials and Generation Z opportunities to engage in information dissemination and social interaction. This research aims to understand the behavior of young voters on social media, particularly platforms like Instagram, and to examine the impact of social media on their political involvement.